Infrared Thermography and Thermal Nondestructive Testing - Vavilov, V. P. Specialist in the field of dosimetry and methodology of nondestructive testing (NDT) Doctor of technical sciences (DSc), Professor of Tomsk Polytechnic University (TPU) 1949- (Springer, 2020)
This is the first book summarizing the theoretical basics of thermal nondestructive testing (TNDT) by combining elements of heat conduction, infrared thermography, and industrial nondestructive testing. The text contains the physical models of TNDT, heat transfer in defective and sound structures, and thermal properties of materials. Also included are the optimization of TNDT procedures, defect characterization, data processing in TNDT, active and passive TNDT systems, as well as elements of statistical data treatment and decision making. This text contains in-depth descriptions of applications in infrared/thermal testing within aerospace, power production, building, as well as the conservation of artistic monuments The book is intended for the industrial specialists who are involved in technical diagnostics and nondestructive testing. It may also be useful for academic researchers, undergraduate, graduate and PhD university students.